2015
DOI: 10.31186/jspi.id.10.1.22-31
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ragi Tape terhadap pH, Bakteri Asam Laktat dan Laktosa Yogurt

Abstract: The objective of this research was to evaluate chemical properties, such as pH, lactic acid bacteria, and lactose levels in yogurt fermented with yeast or yogurt fermented with lactic acid. This research was conducted in November through December 2014 at Gapoktan Sumber Mulya Desa Suka Sari, Kabupaten Kepahiang Provinsi Bengkulu. Experimental design applied in this study was completely randomized design with 3 treatments and 4 replications. P1 = addition of 3% (of 1000 gram milk) plain yogurt starter as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…According to Liu and Tsao (2009) and Octaviana et al (2015) reported that the level of starter concentration used in this study both in the combination of 2 starters and 4 starters will also affect the rate of lactose breakdown at the same incubation time and temperature (60,61). An increase in starter concentration will be followed by increased activity and breeding.…”
Section: Lactose Levelsmentioning
confidence: 76%
“…According to Liu and Tsao (2009) and Octaviana et al (2015) reported that the level of starter concentration used in this study both in the combination of 2 starters and 4 starters will also affect the rate of lactose breakdown at the same incubation time and temperature (60,61). An increase in starter concentration will be followed by increased activity and breeding.…”
Section: Lactose Levelsmentioning
confidence: 76%
“…This is because the microbes found in tape yeast can function as prebiotics and have a positive impact through decreasing pH. Oktaviana et al, (2015), Tape yeast contains types of microorganisms, namely Lactobacillus, Saccharomyces, Streptococcus, Lactococcus, Acetobacter. The positive effects of probiotics Lactobacillus sp.…”
Section: Femur Lengthmentioning
confidence: 99%
“…Di dalam ragi ini, terdapat mikroorganisme yang dapat mengubah karbohidrat (pati) menjadi gula sederhana (glukosa). Karbohidrat (pati) yang difermentasi maka menghasilkan asam laktat yang akan menurunkan nilai pH sehingga menimbulkan rasa asam (Oktaviana et al, 2015).…”
Section: Pendahuluanunclassified